Key strata of mining-induced seismicity in overburden rocks in coal mines and the energy-releasing mechanism of its fracture - Linming DOU; Jinrong CAO; Anye CAO; Wu CAI; Siyuan GONG; Minghe JU; Kunyou ZHOU; Jiliang KAN (Meitan xuebao)
Mining-induced seismicity in strata has become one of the main dynamic phenomena in some coal mines. The theoretical identification of the main controlling rock stratum where mining-induced seismicity occurs is the basis for accurate prevention and control of mining-induced seismicity. In this paper, theoretical analysis, numerical simulation and on-site observation are used. The connotation and type of mining seismic events and mining-induced seismicity are sorted out, and the relationship between mining seismic events and mining-induced seismicity is clarified. The concept of the Key Strata of Mining-induced Seismicity (KSMIS) in overburden rocks is put forward, and the characteristics of the KSMIS are summarized, and the difference between the KSMIS and key strata is presented. The identification method of the KSMIS is proposed, the crack development and energy evolution during the fracture process of the KSMIS are analyzed, and the energy release mechanism for the fracture of the KSMIS is revealed. The results show that: ① Mining seismic events can be classified into micro-seismic events, high-energy seismic events and mining-induced seismicity, and mining-induced seismicity can be classified into overburden rocks, faults, coal pillars, floor, folds and composite types; ② The KSMIS in overburden rocks refers to a layer or group of layers in the roof that control the occurrence and distribution of the mining-induced seismicity, and is classified into two types of high-level and low-level according to the location of the KSMIS; ③ Considering the failure criteria and energy characteristics of thick and hard rock layers, a method of identifying the KSMIS is proposed, and the method is verified by case study; ④ In addition to the crack zones on both sides of the mined area, horizontal shear cracks appeared between the KSMIS and the roof in low position. The strain energy and shear dissipation energy of the interlayer joints were concentrated, and the shear slip between the rock layers occurred. There are strain energy and shear dissipation energy accumulation zones in some areas of the KSMIS, and layering damage exists within the KSMIS; ⑤ When the actual maximum stress of the rock exceeds the strength limit of the rock layer or structural contact surface, the KSMIS will be broken or unstable, resulting in the formation of mining-induced seismicity in overburden rocks. In the process, some of the elastic strain energy and gravitational potential energy is converted into mining-induced seismicity energy as well as various types of dissipation energy, etc. The results of the study can provide theoretical guidance for the prevention and control of mining-induced seismicity in overburden rocks.